Reshaping teaching in higher education : linking teaching with research - Jenkins, Alan, 1940- (Staff and educational development series., 2003)
"The book addresses issues at the individual, course and institutional levels and at the level of national policy. It is written for an international readership. It will be a key work for course leaders, educational developers and policy makers."--Jacket